The Implementation of THE Curriculum 2013 in Mathematics Learning at Grade V SD - Shoriah, Kamilah An; Efendi , Nofriza (The Future of Education Journal, 2022)
This study aims to analyze the problems of implementing the 2013 curriculum in fifth grade mathematics learning at MIS Bakti Dadok Tunggul Hitam, Koto Tangah District, Padang City. This research uses a qualitative approach with a descriptive type. The subjects of this research are fifth grade teachers and students. This research was carried out at MIS Bakti Dadok Tunggul Hitam, Koto Tangah District, Padang on July 19, 2022. The data collection techniques used were field observations, interviews, and documentation. The results showed that in implementing the 2013 curriculum in mathematics lessons in class V not entirely good, because the teacher uses the 2013 curriculum, but for the implementation of the teacher is more dominant using the education unit level curriculum (KTSP) method. In the learning process, students first understand the lesson better if it is explained only one field of study rather than having to be combined with other lessons as used in the 2013 curriculum method. And the three teachers use the media to guide students in the process of understanding mathematics lessons.